Analisis faktor yang memengaruhi pengambilan keputusan pembelian pepaya Calina - Pradana, Anang Kartika; Slamet, Alim Setiawan; Andrianto, M Syaefudin (Jurnal Manajemen, 2018)
Growth of income, healthy awareness and population lead to increase fruit consumption. One of IPB’s successful fruit innovation is Calina papaya. The purpose of this study was to analyze the characteristics of the consumers, and the factors that influence purchases, consumer attitudes toward the attributes and the purchase decision process Calina papaya. Determination number of sampling used slovin and determination of samples used convenience sampling. Analysis methods were using descriptive analysis, factor analysis and analysis multiatribut Fishbein. The results showed that most consumers are housewives who are highly educated purchase based on the needs of nutritional benefits. Information obtained from friends and family. Consumers are satisfied with the Calina papaya. Purchasing decisions are influenced by three main factors, namely social factors and knowledge, individual factors and factors of resources. In terms of attributes, flavor, quality and hygiene products become the most important consideration in the purchase decision process. Peningkatan pendapatan, kesadaran kesehatan dan bertambahnya jumlah penduduk mendorong peningkatan konsumsi buah-buahan. Salah satu inovasi buah sukses IPB adalah pepaya Calina. Tujuan penelitian ini adalah menganalisis karakteristik konsumen, faktor-faktor yang mempengaruhi pembelian, sikap konsumen terhadap atribut serta proses keputusan pembelian pepaya Calina. Penentuan jumlah responden menggunakan pendekatan slovin dan penentuan sampel menggunakan teknik convenience sampling. Analisis data menggunakan analisis deskriptif, analisis faktor dan analisis multiatribut Fishbein. Hasil penelitian menunjukkan bahwa konsumen terbesar adalah ibu rumah tangga yang berpendidikan tinggi, membeli berdasarkan kebutuhan manfaat gizi. Informasi didapat dari teman dan keluarga. Konsumen merasa puas terhadap pepaya Calina. Keputusan pembelian dipengaruhi oleh tiga faktor utama yaitu faktor sosial dan pengetahuan, faktor individu dan faktor sumber informasi. Dari segi atribut, rasa, kualitas dan kebersihan produk menjadi pertimbangan paling penting dalam proses keputusan pembelian.